Whose Grave is this? The Status of Grave Plots in Ancient Greece (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2017)
It is commonly accepted that funerary practices and legislation reflect social and politi- cal structures as well as attitudes to death. But some basic questions have only recently started to attract scholarly attention: Who owned the grave plot? What was its legal status? Were cemeteries administered by any person or group? Was the legal status of a grave situated on private land different from that of a grave in a necropolis? How can we explain burials of non-citizens and slaves in the polis’s territory, if they were de- barred from owning land? Who was responsible for protecting the grave? These ques- tions are of great importance in the study of ancient social and political norms. More- over, they relate to the broader issue of the distinction between ‘public’ and ‘private’ in the Greek polis. This paper re-examines the evidence pertaining to the subject of grave plots’ legal status, so as to offer some tentative answers.